High-light-transmittance semi-permeable electroplating ABS (acrylonitrile butadiene styrene) material as well as preparation method and application thereof

By adjusting the composition and process flow of ABS resin, a semi-permeable electroplating ABS material with high light transmittance was developed, which solved the problems of complex injection molding process and difficult control of laser engraving in the existing technology, and achieved excellent electroplating performance and high transparency of the material. Light performance, suitable for a variety of application scenarios.

CN119286176APending Publication Date: 2025-01-10SHANGHAI KUMHO SUNNY PLASTICS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411346955.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Prior Art When developing translucent electroplating ABS materials for automotive and lighting products, there is a complex injection molding process that limits structural design. The thickness of the radium carving is not easy to control, resulting in rough pattern edges, affecting clarity, and reducing the toughness and roughness of the material. .

Method used

Using semi-permeable ABS material with high light transmittance, the butadiene content, rubber particle size, crosslinking degree and refractive index of ABS resin is used, and the MAS copolymer and maleic anhydride graft copolymer are combined as dispersion aids. , improve the dispersion performance of the material and the plating binding force, use a twin screw extruder for uniform mixing and extrusion, followed by water tank cooling and pelletization, and finally drying and injection molding in a blower oven.

Benefits of technology

It realizes excellent electroplating performance and high light transmission performance of the material. It is suitable for light transmission electroplating trim for automobiles, lighting products and household appliances, improving the transparency and electroplating bonding of the material, reducing production costs and process complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005061231630000021
    Figure BDA0005061231630000021
  • Figure BDA0005061231630000041
    Figure BDA0005061231630000041
  • Figure BDA0005061231630000051
    Figure BDA0005061231630000051
Patent Text Reader

Abstract

The invention relates to a high-light-transmittance semi-permeable electroplating ABS (Acrylonitrile Butadiene Styrene) material as well as a preparation method and application thereof. The high-light-transmittance semi-permeable electroplating ABS material is prepared from the following components in parts by weight: 25 to 35 parts of ABS high rubber powder, 40 to 60 parts of MAS copolymer resin, 5 to 10 parts of transparent ABS resin, 5 to 10 parts of dispersing aid, 0.1 to 0.4 part of antioxidant and 0.1 to 0.3 part of lubricant. Compared with the prior art, the prepared electroplating ABS material has high light transmittance performance and is suitable for electroplating workpieces with optical requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials and relates to a semi-transparent electroplated ABS material with high light transmittance and a preparation method and application thereof. Background Art

[0002] Nowadays, with the development of the new energy vehicle market, consumers have put forward more demands for the personalization of cars while pursuing the functionality of cars. In car design, in addition to appearance and color, some detailed decorative parts also play an important role. Among them, luminous decorative parts with unique lighting design can enhance the modern, technological and advanced sense of the vehicle, and increase recognition and visual appeal.

[0003] Buttons and car logos and other electroplated parts can also achieve luminous effects. After the electroplated material and the transparent material are double-molded, the electroplated layer is removed together with the electroplated material by laser engraving to expose the transparent material layer. After adding lamp beads inside the parts, the luminous effect can be achieved. However, on the one hand, the complex injection molding process limits the structural design of the parts; on the other hand, it is necessary to laser engrave a material layer with a thickness of 1-2mm at the same time. The laser energy is high and difficult to control. If the laser engraves a complex pattern, the edges will be rough, affecting the clarity of the pattern, so complex pattern design is impossible.

[0004] Xu Lu and others mentioned in the document "Research Progress of Transparent ABS Resin" that there are two ways to obtain light transmittance of ABS resin: one is to match the refractive index of the rubber dispersed phase and the matrix resin phase to reduce the light scattering effect to make it transparent, thereby obtaining transparent ABS resin; the other is to make the rubber particle size smaller than the wavelength of visible light, at which time the dispersed and continuous phases are optically close to uniform, and the ABS resin can also be transparent. In order to reduce the refractive index of the SAN resin phase, polymethyl methacrylate (1.492) and polybutyl acrylate (1.524) with a lower refractive index can be introduced as a refractive index regulator for adjustment. Finally, the difference in the refractive index between the dispersed phase and the continuous phase is less than 0.009, and the ABS resin can be transparent.

[0005] However, reducing the size of the rubber phase in the electroplated ABS resin will reduce the toughness of the material, resulting in the risk of fracture of the electroplated parts. In addition, introducing an excessive amount of the third phase (MMA) that cannot be roughened will seriously reduce the roughening performance of the electroplated material, resulting in insufficient roughening and causing missed plating of the electroplated parts.

[0006] Therefore, it is necessary to develop electroplated ABS materials specifically for light-transmitting plated parts to meet the demand for light-transmitting plated materials in the automotive, lighting products, home appliances and other market sectors. Summary of the invention

[0007] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a semi-transparent electroplated ABS material with high light transmittance and its preparation method and application, which has excellent electroplating performance and high light transmittance.

[0008] The purpose of the present invention can be achieved by the following technical solutions:

[0009] In a first aspect, the present invention provides a semi-transparent electroplated ABS material with high light transmittance, comprising the following raw material components in parts by weight:

[0010]

[0011] Furthermore, in the ABS high-rubber powder, the content of butadiene is 25-60wt%, and the number average molecular weight is 100,000-150,000.

[0012] Furthermore, the ABS high-rubber powder is ABS with a butadiene rubber content of more than 40%, a crosslinking degree of 60-80wt%, and a particle size of the butadiene rubber contained in the ABS of preferably 100-300nm, more preferably 100-150nm.

[0013] Furthermore, the transparent ABS resin has a refractive index of 1.51-1.54, a melt flow rate (under the condition of 220° C.*10 kg) of 10-20 g / min, and is grafted with MMA groups with a grafting rate of 20-30%.

[0014] Furthermore, the MAS copolymer resin is methyl methacrylate-styrene-acrylonitrile, wherein the proportion of MMA is 30-40wt%.

[0015] Furthermore, the dispersing aid is one or more maleic anhydride graft copolymers containing styrene.

[0016] Furthermore, the dispersing aid is one or a combination of styrene-g-maleic anhydride and styrene-acrylonitrile-g-maleic anhydride. Preferably, the content of maleic anhydride groups is 7-20wt%.

[0017] Furthermore, the semi-transparent electroplated ABS material also includes the following raw material components in parts by weight:

[0018] Antioxidant 0.1-0.4 parts;

[0019] Lubricant 0.1-0.3 parts.

[0020] Furthermore, the antioxidant is one or more of polyphenol antioxidants and phosphate antioxidants.

[0021] Furthermore, the lubricant is one or more of vinyl bis stearamide and pentaerythritol stearate lubricants.

[0022] In a second aspect, the present invention provides a method for preparing a semi-transparent electroplated ABS material with high light transmittance, comprising the following steps:

[0023] (1) Weighing each raw material component according to a weight ratio, mixing them evenly, and obtaining a mixed raw material;

[0024] (2) Add the mixed raw materials into a twin-screw extruder, control the speed to 400-600 rpm, the feeding section temperature to 210-220° C., the plasticizing section temperature to 220° C.-230° C., the extrusion temperature to 230-240° C., and the pressure to 2-4 MPa. After melt blending, the extruded material strips are cooled in a water tank and pelletized to obtain the product.

[0025] In a third aspect, the present invention also provides an application of a semi-transparent electroplated ABS material with high light transmittance in a light-transmitting electroplated part.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] 1. The ABS material of the present invention has excellent electroplating performance and high light transmittance, and is suitable for light-transmitting electroplating trims of automobiles, lighting products, and household appliances.

[0028] 2. The ABS resin used in the present invention has a low molecular weight and a cross-linking degree of 60-80%. The low cross-linking degree helps the rubber powder to be evenly dispersed in the substrate, is not easy to agglomerate, and is more easily coarsened; the particle size of butadiene rubber is 100-300nm, which is lower than the wavelength of visible light (880-380nm), which will affect the propagation mode of light and produce a diffraction effect, so that the light can partially bypass the rubber powder, and the visual effect increases the light transmittance or blurred transparency.

[0029] 3. The ABS resin used in the present invention is grafted with some MMA groups. On the one hand, the comprehensive refractive index of the grafted ABS is reduced and becomes closer to that of the MSA resin, thereby increasing light transmittance. On the other hand, the compatibility of ABS and MSA is improved, thereby making ABS more evenly dispersed in MSA.

[0030] 4. The present invention uses maleic anhydride graft copolymer containing styrene as a dispersing aid, which greatly improves the dispersibility of the rubber powder. The rubber powder is more evenly dispersed, so it is easier to be roughened and etched by the roughening liquid. The toughness of the small-particle rubber powder is improved, and the reduction of the roughening performance by MMA is reduced, so that the electroplating bonding strength of the material is increased.

[0031] 5. The semi-transparent electroplated ABS material with high light transmittance of the present invention has low cost, simple production process and high cost performance. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0033] The raw materials used in the following examples and comparative examples are:

[0034] ABS resin 1: Kumho Petrochemical Co., Ltd., South Korea, brand name P / D181, butadiene rubber particle size 370nm; ABS resin 2: Kumho Petrochemical Co., Ltd., South Korea, brand name P / D192, butadiene rubber particle size 100nm; ABS resin 3: Shandong Wanda Chemical Co., Ltd., brand name WD132, butadiene rubber particle size 300nm; MAS resin: Donghai Plastic Co., Ltd., brand name W1822; Transparent additive (i.e. transparent ABS resin ): Zhenjiang Chimei Chemical Co., Ltd., brand name PA758; Dispersing aid 1: Crayville (Guangzhou) Chemical Co., Ltd., styrene grafted maleic anhydride copolymer, brand name SMA1440; Dispersing aid 2, Shanghai Rizhisheng Technology Co., Ltd., styrene-acrylonitrile-glycidyl methacrylate copolymer, brand name SAG001; Hindered phenol antioxidant: BASF AG, brand name IG-1076; Phosphate ester antioxidant: Chemtura, brand name Ultranox 626; Lubricant: Emuri Oil Chemical Company, brand name P861.

[0035] Table 1 Composition of semi-transparent electroplated ABS composition

[0036]

[0037] Comparative Examples 1-4 and Examples 1-6

[0038] Dry the ABS resin at 90-100°C for 2-3 hours and set aside; dry the MAS resin at 90-100°C for 4-6 hours and set aside.

[0039] 1) Weigh ABS resin, MAS resin, transparent ABS resin, dispersing aid, antioxidant and lubricant according to the weight ratio in Table 1, and mix them evenly;

[0040] 2) The raw materials mixed in step 1) are blended and granulated through a twin-screw extruder, the extruder speed is 600 rpm, the feeding section temperature is 210° C., the plasticizing section temperature is 230° C., the extrusion temperature is 245° C., and the pressure is 3 MPa. After melt blending, the extruded material strips are cooled in a water tank and then pelletized to obtain the product.

[0041] Among them, the length-to-diameter ratio of the extruder screw used in the twin-screw extruder is 44:1.

[0042] The above product was dried in a blast oven at 85°C for 5 hours and then injection molded into a standard specimen standard smooth plate (150mm*100mm*3mm) using a plastic injection molding machine at an injection temperature of 250°C.

[0043] The above standard smooth plate was roughened, the roughening solution temperature was 70°C, and the roughening time was 10 min.

[0044] The roughened standard plain board is electroplated, with the copper layer having a thickness of 21±1 μm and the chromium layer having a thickness of 15±1 μm.

[0045] The materials obtained from Comparative Example 1 and Examples 1-6 were subjected to performance tests, and the test results are shown in Table 2.

[0046] Light transmittance test: According to ASTM D1003-13 standard, the light transmittance test was performed using a roughened 3.0 mm standard light plate.

[0047] Electroplating bonding strength test: According to DIN EN 1464 standard, the electroplated standard bare board is cut into 10mm*150mm*3mm specimens for electroplating bonding strength test.

[0048] Heat resistance test: According to the TL528 electroplated ABS heat resistance standard, the electroplated standard bare board was placed in a 100℃ oven for 6 hours for heat resistance test.

[0049] Cross-hatch performance after heat aging: According to the TL528 electroplated ABS heat resistance standard, the standard bare board after heat aging is subjected to a cross-hatch test. If the mark falls off after the cross-hatch, it is NG, and if it does not fall off, it is OK.

[0050] Table 2 Properties of semi-transparent electroplated ABS

[0051]

[0052]

[0053] It can be seen from the transmittance test results that in Comparative Example 3, Comparative Example 4 and Examples 1-6 in which transparent ABS resin is added, the transparency is higher than that in Comparative Example 1-2 without transparent ABS resin; in addition, in Examples 1-3 in which different contents of ABS resin 2 are added with the same total amount of glue, the higher the proportion of small-particle ABS resin 2, the higher the transparency; among Examples 3 and 5 in which different contents of dispersing aid are added, Example 5 with a higher content of dispersing aid has a higher transparency, indicating that the dispersing aid containing maleic anhydride group (MAH) structure and the small-particle rubber powder have a synergistic effect on improving the transparency in the transparent ABS material.

[0054] It can be seen from the results of the electroplating bonding test that in Comparative Example 2 and Examples 1-6 in which a dispersing aid is added, the electroplating bonding strength is higher than that in Comparative Examples 1 and 3 in which no dispersing aid is added; among them, in Examples 3 and 5 in which different amounts of dispersing aid are added, the higher the content of the dispersing aid, the higher the electroplating bonding strength; in addition, it can be seen from Examples 1-3 that the addition of ABS resin 2 reduces the average particle size of the rubber in the material, and the material with a smaller rubber particle size is easier to be coarsened, and the electroplating bonding strength increases.

[0055] Compared with Example 5, Comparative Example 4 is mostly the same, except for the introduction of a dispersing aid containing glycidyl methacrylate (GMA). The addition of the dispersing aid slightly improves the transparency of the material, but due to the lack of MAH structure, there is no synergistic effect, the electroplating performance is poor, the bonding strength is equivalent to that of Comparative Example 3, and the cross-hatch test after thermal aging is NG.

[0056] The roughening conditions are a roughening liquid temperature of 70°C and a roughening time of 10 minutes. During the roughening process, the rubber on the ABS resin is etched by the roughening liquid to produce a dovetail hole structure of moderate size. In the present invention, the polar maleic anhydride group in the dispersing aid containing the MAH structure can react with the ABS with weak polarity to prevent the agglomeration and entanglement of the ABS rubber powder, making the rubber powder dispersed more evenly, and synergistically act with the small-particle rubber to further reduce the domain size of the ABS sea island phase; on the one hand, the domain size is reduced to below the wavelength of visible light (880-380nm), which will affect the propagation mode of light and produce a diffraction effect, so that the light can partially bypass the rubber powder, and the visual effect increases the light transmittance or blurred transparency; on the other hand, after the domain size is reduced, the specific surface area increases, and it is easier to be roughened and etched by the roughening liquid, forming more hollow structures, reducing the reduction of the roughening performance by MMA, and increasing the electroplating bonding force of the material.

[0057] In addition, the transmittance, electroplating performance, and heat resistance of Examples 5 and 6 are comparable, indicating that the addition of processing aids has no effect on the transmittance, electroplating performance, and heat resistance of the material.

[0058] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A semi-transparent electroplated ABS material with high light transmittance, characterized in that: The raw material components include the following parts by weight:

2. The semi-transparent electroplated ABS material with high light transmittance according to claim 1, characterized in that: The ABS high-rubber powder has a butadiene content of 25-60wt% and a weight-average molecular weight of 100,000-150,000; The ABS high-rubber powder is ABS with a butadiene rubber content of more than 40%, a cross-linking degree of 60-80%, and a particle size of the butadiene rubber contained in the ABS of 100-300nm.

3. The semi-transparent electroplated ABS material with high light transmittance according to claim 1, characterized in that: The transparent ABS resin has a refractive index of 1.51-1.54 and a melt flow rate of 10-20 g / min. It is grafted with MMA groups, and the grafting rate is 20-30%.

4. The semi-transparent electroplated ABS material with high light transmittance according to claim 1, characterized in that: The MAS copolymer resin is methyl methacrylate-styrene-acrylonitrile, wherein the proportion of MMA is 30-40wt%.

5. The semi-transparent electroplated ABS material with high light transmittance according to claim 1, characterized in that: The dispersing aid is one or more maleic anhydride-type graft copolymers containing styrene.

6. The semi-transparent electroplated ABS material with high light transmittance according to claim 5, characterized in that: The dispersing aid is one of styrene-g-maleic anhydride and styrene-acrylonitrile-g-maleic anhydride or a combination of two thereof.

7. The semi-transparent electroplated ABS material with high light transmittance according to claim 1, characterized in that: Also includes the following raw material components in parts by weight: Antioxidant 0.1-0.4 parts; Lubricant 0.1-0.3 parts.

8. The semi-transparent electroplated ABS material with high light transmittance according to claim 7, characterized in that: The antioxidant is one or more of polyphenol antioxidants and phosphate antioxidants; The lubricant is one or more of vinyl bis stearamide and pentaerythritol stearate lubricants.

9. The method for preparing a semi-transparent electroplated ABS material with high light transmittance according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Weighing each raw material component according to a weight ratio, mixing them evenly, and obtaining a mixed raw material; (2) Add the mixed raw materials into a twin-screw extruder, control the speed to 400-600 rpm, the feeding section temperature to 210-220° C., the plasticizing section temperature to 220° C.-230° C., the extrusion temperature to 230-240° C., and the pressure to 2-4 MPa. After melt blending, the extruded material strips are cooled in a water tank and pelletized to obtain the product.

10. Use of the semi-transparent electroplated ABS material with high light transmittance as described in any one of claims 1 to 8 in light-transmitting electroplated parts.

Citation Information

Cited By

  • Semi-transparent electroplated ABS material having high light transmittance, preparation method therefor, and use thereof

    WO2026066634A1